Implementasi Seni Gerak Dan Tari Untuk Membentuk Karakter Anak di Paud - Hida Zahra Lubis; Fadhila Husna; Melvi Sari Anggraini; Rizka Khairi (Journal of Cultural Relativism (JCR), 2025)
Early character education provides a strong foundation for developing a resilient and optimistic character. Dance and movement arts are powerful tools for fostering moral principles. The purpose of this study was to examine how dance and movement arts are used to develop children's character in Early Childhood Education (PAUD). A descriptive qualitative research methodology was used, and data were collected through documentation, interviews, and observations. The findings of the study indicate that dance and movement arts activities in early childhood can help develop character traits such as self-control, teamwork, discipline, and tolerance. Curious, expressive, and appreciative strategies that are tailored to the child's developmental stage are needed for effective implementation.